Rational Coformer Selection in the Development of 6-Propyl-2-thiouracil Pharmaceutical Cocrystals - Francisco Javier Acebedo-Martínez; Carolina Alarcón-Payer; Cristóbal Verdugo-Escamilla; Jesús Martín; Antonio Frontera; Alicia Domínguez-Martín; Jaime Gómez-Morales; Duane Choquesillo-Lazarte (MDPI AG, 2023)
Pharmaceutical multicomponent solids have proved to efficiently modulate the physicochemical properties of active pharmaceutical ingredients. In this context, polyphenols are interesting coformers for designing pharmaceutical cocrystals due to their wide safety profile and interesting antioxidant properties. The novel 6-propyl-2-thiouracil multicomponent solids have been obtained by mechanochemical synthesis and fully characterized by powder and single-crystal X-ray diffraction methods. The analysis of supramolecular synthons has been further performed with computational methods, with both results revealing a robust supramolecular organization influenced by the different positions of the hydroxyl groups within the polyphenolic coformers. All novel 6-propyl-2-thiouracil cocrystals show an enhanced solubility profile, but unfortunately, their thermodynamic stability in aqueous media is limited to 24 h.